1998
DOI: 10.3141/1635-09
|View full text |Cite
|
Sign up to set email alerts
|

Applying the Ordered Probit Model to Injury Severity in Truck-Passenger Car Rear-End Collisions

Abstract: Collisions between heavy trucks and passenger cars are a major concern because of the severity of injuries. This research has two objectives. One is to examine the impact of various factors on injuries to passenger car occupants involved in such collisions. Due to the complex interaction of factors influencing injury levels in truck-car collisions, the ordered probit model is used to identify specific variables significantly influencing levels of injury in two-vehicle rear-end involvements on divided roadways.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
98
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(105 citation statements)
references
References 6 publications
5
98
0
2
Order By: Relevance
“…Our results suggest that wet road surface conditions reduce the level of M25 crash severity compared with dry surface conditions. This finding is consistent with other studies (e.g., Quddus et al, 2002;Duncan et al, 1998;Shankar and Mannering, 1996). Quddus et al (2002) argued that this is likely to be an effect of reduced speed levels.…”
Section: Figure 3 Is About Heresupporting
confidence: 83%
“…Our results suggest that wet road surface conditions reduce the level of M25 crash severity compared with dry surface conditions. This finding is consistent with other studies (e.g., Quddus et al, 2002;Duncan et al, 1998;Shankar and Mannering, 1996). Quddus et al (2002) argued that this is likely to be an effect of reduced speed levels.…”
Section: Figure 3 Is About Heresupporting
confidence: 83%
“…A review of the studies indicated that many researchers used ordered probit models to examine injury severities in highway crashes (O'Donnell and Connor 1996, Abdel-Aty 2003, and Duncan et al 1999. However, use of such models to examine severity of rural highway crashes is rare.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Injury severity probabilities for accidents involving young male drivers are also predicted using the estimated ordered probit models as suggested by O'Donnell and Connor (1996), Duncan et al (1998), andQuddus et al (2002).…”
Section: Table 1 Is About Herementioning
confidence: 99%